1987
DOI: 10.1523/jneurosci.07-07-02129.1987
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of dopamine in the caudate nucleus but not in nucleus accumbens impairs reaction-time performance in rats

Abstract: Impairment of the dopaminergic system in the brain induced by dopamine-receptor antagonists or by specific neurotoxin terminal lesions results in motor disturbances in rats. In order to specify further the role of the different dopamine pathways in the brain on motor function, the performance of rats trained in an operant reaction-time task was examined after systemic administration of a dopamine-receptor antagonist, alpha-flupenthixol, and after specific destruction of dopamine neurons by 6-hydroxydopamine pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
108
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(121 citation statements)
references
References 18 publications
11
108
2
Order By: Relevance
“…Previous investigators examining the effect of large bilateral depletion of striatal DA observed disruptions in reaction time performance, suggestive of difficulty with movement initiation (Amalric and Koob 1987;Amalric et al 1995;Moukhles et al 1994). In agreement, we also observed deficits that were associated with a preponderant loss of DA (у60%) in the striatum in comparison to the other brain structures innervated by the MFB.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous investigators examining the effect of large bilateral depletion of striatal DA observed disruptions in reaction time performance, suggestive of difficulty with movement initiation (Amalric and Koob 1987;Amalric et al 1995;Moukhles et al 1994). In agreement, we also observed deficits that were associated with a preponderant loss of DA (у60%) in the striatum in comparison to the other brain structures innervated by the MFB.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, these animals did sustain a significant depletion of DA in limbic structures, particularly the nucleus accumbens, a brain region shown to be involved in reward and motivation. However, 6-OHDA lesions of the nucleus accumbens are reported not to have an effect on performance in the reaction time task (Amalric and Koob 1987). Moreover, we observed that animals in this group had difficulty handling the food pellet and would normally, without much success, attempt to consume the pellet while it was still in the food trough.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The CP but not the ACC has been implicated in the initiation of rapid responses, because even moderate DA depletion of the CP impaired RT performance in rats (Amalric and Koob 1987). The medial subregion of the CP seems to be important for rapid movement initiation, since neurotoxic lesions of the medial but not of the lateral CP impaired RT performance of rats in the RT task used in the present study (Hauber and Schmidt 1994) and other RT tasks (Brown and Robbins 1989).…”
Section: Discussionmentioning
confidence: 61%
“…The effects of an intra-NAc NMDA and dopamine D 2 receptor blockade were examined in a lever release task for rats in which RTs of instrumental responses were a function of the expected food reward signaled in advance by discriminative instructive stimuli. Although it is well known that striatal NMDA and dopamine receptors play a key role in motor control (Hauber, 1996(Hauber, , 1998, the NAc does not control motor aspects of RT performance per se (Amalric and Koob, 1987;Brown and Robbins, 1989;Carli et al, 1989). Thus alterations of RTs induced by intra-NAc blockade of NMDA and dopamine D 2 receptors should reflect changes in the translation of motivational information into response speed.…”
mentioning
confidence: 99%